Developing a Problem-Oriented Policing Model in Ada County, Idaho, 1997-1998 - Crank, John P. ([Verlag nicht ermittelbar], 1999)
To explore the idea of community policing and to get an understanding of citizens' policing needs, representatives from the Ada County Sheriff's Office and Boise State University formed a research partnership and conducted surveys of county residents and sheriff's deputies. The county-wide survey of residents (Part 1) was designed to enhance the sheriff's current community policing program and to assist in the deployment of community policing officers by measuring citizens' perceptions and fear of crime, perceptions of deputies, knowledge of sheriff's services, and support for community policing. Questions in the citizen survey focused on feelings of safety in Ada County, such as perception of drugs, gangs, safety of youth, and safety at night, satisfaction with the Sheriff's Office, including ratings of the friendliness and fairness of the department and how well deputies and citizens worked together, attitudes regarding community-oriented policing, such as whether this type of policing would be a good use of resources and would reduce crime, and neighborhood problems, including how problematic auto theft, vandalism, physical decay, and excessive noise were for citizens. Other questions were asked regarding the sheriff's deputy website, including whether citizens would like the site to post current crime reports, and whether the site should have more information about the jail. Respondents were also queried about their encounters with police, including their ratings of recent services they received for traffic violations, requests for service, and visits to the jail, and familiarity with several programs, such as the inmate substance abuse program and the employee robbery prevention program. Demographic variables in the citizen survey include ethnicity, gender, level of schooling, occupation, income, age, and length of time residing in Ada County. The second survey (Part 2), created for the sheriff's deputies, used questions from the citizen survey about the Sheriff's Office service needs. Deputies were asked to respond to questions in the way they thought that citizens would answer these same questions in the citizen survey. The purpose was to investigate the extent to which sheriff's deputies' attitudes mirrored citizens' attitudes about the quality of service.